Pengelolaan Zakat Infak Shodaqah (Studi Pada NU CARE-LAZISNU dan LAZISMU Kabupaten Magelang) - M Pudail; Tolkhah Alwi (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2020)
The population of Indonesian Muslims is very large, based on the 2010 census, adherents of Islam in Indonesia are 207,176,162 people or 87.18% of the total population of Indonesia, this certainly has an impact on the potential for receiving and collecting Zakat, Infak and Sodaqah (ZIS). There are several amil zakat institutions that are legal and recognized by the people of Indonesia, for example LazisNu under the auspices of the Nahdlatul Ulama organization and LazisMu under the auspices of the Muhammadiyah organization. This study aims to determine the differences in ZIS management at NU CARE-LAZISNU and LAZISMU in Magelang Regency, both in terms of collection management, ZIS management management, and ZIS distribution management. This study uses a qualitative method using primary data and secondary data. The results of this study are in general the management of ZIS management at NU Care-LAZISNU and LAZISMU in Magelang Regency has different characteristics but there are some similarities in several aspects. In the collection management, NU Care-LAZISNU Magelang Regency uses the direct and indirect collection method by prioritizing the NU KOIN movement as the main program, while LAZISMU Magelang Regency uses the direct and indirect collection method by selling all its programs. In management, NU Care- LAZISNU Magelang Regency has a management structure at the District and Village levels using a decentralized pattern, while LAZISMU Magelang Regency has representatives at the sub-district level and 8 service offices whose task is to collect ZIS funds from the community using a centralized management pattern. In terms of distribution, NU Care-LAZISNU in Magelang Regency carried out in collaboration with the Autonomous Body and other institutions under the auspices of Nahdlatul Ulama, while LAZIMU in Magelang Regency is carried out directly by it self.